Slope intercept form: y=mx+b, with m being the slope and b being the y-intercept.
Plug 4 in for the slope, as that's given in the question:
y=4x+b
Now, we need to solve for the y-intercept, because the answer could be B, C, or D. You can do this by plugging in the given coordinate (-1,8) for x and y in the equation respectively.
8=4(-1)+b
Multiply.
8=-4+b
Add four to both sides.
12=b
The y-intercept is 12. Plug 12 into the equation for b:
y=4x+12 is the completed equation.
The answer is C.
I hope this helps :)
Answer:
y = 4x + 7
Step-by-step explanation:
parallel = same slope
y = 4x + b
plug in (-4, -9)
-9 = 4(-4) + b
-9 = -16 + b
b = 7
y = 4x + 7
Answer:
7=4x+7
Step-by-step explanation:
To do this you would just plug in (-4,-9) into the equation y=mx+b so we would get -9=4(-4)+b when you simplify you will get -9=-16+b so we would add 16 to both sides and we would get 7=b so we would know that the y intercept is 7 and we know that if a line is parallel to another line is just has a different b so for our equation we would get 7=4x+7
Answer:
243.875 is 243.9 (rounded to nearest tenth)
243.875 is 243.88 (rounded to nearest hundredth)
243.875 is 240 (rounded to nearest tents)
243.875 is 200 (rounded to nearest hundred)
Step-by-step explanation:
To round a number, we look at the number next to the place value. If the number is more than or equal to 5 then add 1 with the place value.
243.875 to nearest tenth, hundredth, ten, and hundred.
2 is in hundreds place
4 is in tens place
3 is in ones place
8 is in tenth place
7 is in hundredth place
5 is in thousandth place
243.875 is 243.9 (rounded to nearest tenth)
243.875 is 243.88 (rounded to nearest hundredth)
243.875 is 240 (rounded to nearest tents)
243.875 is 200 (rounded to nearest hundred)
(-y2 – 4y - 8) – (-4y2 – 6y + 3)
Answer:
3y^2 +2y -11
Step-by-step explanation:
(-y^2 – 4y - 8) – (-4y^2 – 6y + 3)
Distribute the minus sign
(-y^2 – 4y - 8) +4y^2 + 6y - 3
Combine like terms
-y^2+4y^2 – 4y + 6y - 3-8
3y^2 +2y -11
Answer:
3y^2+2y-11
Step-by-step explanation:
I am guessing for -y2 and -4y2 you meant exponents; it would still get you the same answer though.
-y^2-4y-8 - (-4y2-6y+3)
1.Distribute; -y^2-4y-8 -1(-4y2*-1-6y*-1+3*-1)
you then get; -y^2+(-4y)+(-8) +4y^2+6y+-3
2.Combine like terms; 3y^2+2y-11
Then you get: 3y^2+2y-11.